POTENSI TUMBUHAN DAN SEBARAN TANAMAN BIOPESTISIDA DI KAMPUS UNIVERSITAS RIAU - Agus Sutikno; Defri Yoza; Viny Volcherina Darlis (JURNAL ILMU-ILMU KEHUTANAN, 2020)
This study aims to determine the potential of plants as biopesticides found around Riau University campus. The method used consists of vegetation analysis and renaissance methods.  The vegetation analysis method was used in the arboretum area of the Riau University while the renaissance survey was carried out on agricultural gardens, shrubs, and road shade plants. From the survey results, there were 25 types of botanical pesticides with the highest growth rate at the seedling and understorey plants.